2021
DOI: 10.1002/adhm.202102070
|View full text |Cite
|
Sign up to set email alerts
|

A Naked Eye‐Invisible Ratiometric Fluorescent Microneedle Tattoo for Real‐Time Monitoring of Inflammatory Skin Conditions

Abstract: The field of portable healthcare monitoring devices has an urgent need for the development of real‐time, noninvasive sensing and detection methods for various physiological analytes. Currently, transdermal sensing techniques are severely limited in scope (i.e., measurement of heart rate or sweat composition), or else tend to be invasive, often needing to be performed in a clinical setting. This study proposes a minimally invasive alternative strategy, consisting of using dissolving polymeric microneedles to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 95 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…Although light and thermal stimuli serve as examples in this study, prior research has demonstrated novel chemistries and technologies for materials that respond to a broad range of different stimuli of interest in medicine and other applications, including glucose, enzymes, and pH ( Deirram et al., 2019 ; Kowalski et al., 2018 ; Linsley and Wu, 2017 ; Mu et al., 2018 ; Municoy et al., 2020 ; Ward and Georgiou, 2011 ; Wu et al., 2011 ). These functional materials and particles may be loaded into MN patches and delivered into the skin to monitor a variety of different physiological parameters ( Babity et al., 2022 ; He et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although light and thermal stimuli serve as examples in this study, prior research has demonstrated novel chemistries and technologies for materials that respond to a broad range of different stimuli of interest in medicine and other applications, including glucose, enzymes, and pH ( Deirram et al., 2019 ; Kowalski et al., 2018 ; Linsley and Wu, 2017 ; Mu et al., 2018 ; Municoy et al., 2020 ; Ward and Georgiou, 2011 ; Wu et al., 2011 ). These functional materials and particles may be loaded into MN patches and delivered into the skin to monitor a variety of different physiological parameters ( Babity et al., 2022 ; He et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Allowing intradermal administration for the quantitative monitoring of physiological and pathological parameters remotely without requiring trained personnel and complex instrumentation. For instance, its use was recently illustrated for the non-invasive monitoring of dermal inflammatory conditions [6]. Thus, it will be of great help for researchers and clinicians working with dermally injected fluorescent tracers.…”
Section: Discussionmentioning
confidence: 99%
“…The marker samples were purchased either from Lumiprobe or synthesized by the Faculty of Pharmacy at the Université de Montréal. Synthesis and characterization are described in [6]. Dilution series in Ethanol for the fluorescent markers Cy3, Cy5 and Cy7.5 were prepared to gather first data regarding the fluorescence intensity meter's performance.…”
Section: Experimental Device Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…An electrochemical sensor is an apparatus that converts the chemical quantity of a sample and into an electrical quantity based on the electrochemical property of the sample and to perform sensing detection [ 15 ]. Among these, miniaturized electrochemical sensors can be integrated in many types of wearable substrates; for example, electrochemical sensors integrated on microneedle patches can reach the dermal matrix fluid of human and animal skin for the systemic transdermal detection of various analytes [ 16 ]. In the wake of the development of microelectromechanical system (MEMS) technology [ 17 ], many miniaturized electrochemical sensors combined with microneedles have produced a variety of electrochemical microneedle sensors for monitoring biomarkers.…”
Section: Introductionmentioning
confidence: 99%